Hydroclimate change in subtropical South Africa during the mid-Piacenzian warm period - Zhao, Xueqin; Koutsodendris, Andreas; Caley, Thibaut; Dupont, Lydie (Quaternary science reviews, 2020)
The mid-Piacenzian Warm Period (mPWP, 3.264-3.025 Ma) of the Pliocene epoch has been proposed as an analog for future climate scenarios. Disagreement between the paleoenvironmental reconstruction and model simulations of the climate in subtropical regions for this period suggests that more investigation of the subtropical climate variability of the mPWP is needed. This study presents pollen, microcharcoal and benthic foraminifera oxygen isotope records generated from marine sediment cores of International Ocean Discovery Program (IODP) Exp. 361 Site U1479 from the Cape Basin offshore of South Africa for the period between 3.337 and 2.875 Ma. With an average sample resolution of 3 ka, this record represents the highest-resolution record of mPWP vegetation change from the region. Our results indicate that the vegetation during the mPWP was dominated by fynbos (species-rich heathy vegetation in the Cape Floristic Region) with variable proportions of Ericaceae. Moreover, the development of the Afrotemperate forest (tall, multilayered indigenous forests in South Africa) reflects shifts in the amounts of precipitation between winter and summer in the year-round rainfall zone. The vegetation variation is probably influenced by the latitudinal insolation gradient in response to precession forcing. Several glacials depicted by the benthic foraminifera oxygen isotope record were characterized by lower percentage values of Restionaceae, higher percentage values of ericoid fynbos and Afrotemperate forest. These events correspond well with cooler SE Atlantic sea surface temperatures driven by interactions of both atmospheric and oceanographic processes. The cooler sea surface temperatures attributed to Antarctic ice sheet expansion, reduced Agulhas leakage (heat and salt transfer from the Indian Ocean to the Atlantic Ocean) and/or intensified southern Benguela upwelling, resulted in less precipitation in the winter rainfall zone of South Africa.
Gesehen am 23.12.2020